(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Maxsurf software is a software that can help in simulating modeling aspects, especially marine vehicles. However, the modeling is still limited to large-dimensional marine vehicles. The aim of this study was to map the potential use of Maxsurf software as a simulation tool for small marine vessels used by fishermen. The mapping was conducted by reviewing articles related to Maxsurf’s use based on its modeling, resistance, and stability.The research method used is a Publish or Perish literature search and VOSviewer bibliometric analysis. Articles on the use of Maxsurf software from 2015-2025 were obtained from international journals indexed by Google Scholar and Scopus, with the main keyword Maxsurf. The search results on Publish or Perish obtained 42 articles related to the use of maxsurf on large-dimension ships. The distribution of maxsurf use is found in 42 articles with 7 articles (2022 and 2021), 6 articles (2025, 2023, and 2020), 3 articles (2018), 4 article (2024), and 1 article (2019, 2016, and 2015). The general topic studied in the research is design analysis with the most frequently used maxsurf, namely the combination of maxsurf modeller – resistance in 18 article. Research trends are visualized using VOSviewer with the relationship between research topics and keywords. There are 6 main clusters, including; cluster 1 (12); cluster 2 (5); cluster 3 (2); cluster 4 (9); cluster 5 (10); cluster 6 (11). This phenomenon shows that the distribution of topics is still low by looking at the research trend which has decreased over the past 10 years.